Investors’ Perception towards IPO in Khairahani Municipality, Chitwan - Kandel, Bijaya (Journal of Bhuwanishankar, 2022)
The most important aspect of a company is its Initial Public Offering (IPO). The company’s performance, the sector’s performance, promoters’ background, pricing mechanism, allotment procedures, the legal policy of SEBON, and market information are factors affecting IPO investment. In this context, this study attempted to explore the investors’ perception towards allocating 10 units of IPO and Book Building System as well as to examine the factors that affect the investors’ perception of IPO investment. The researcher employed the descriptive exploratory research design to reach the ontology of the issue. The study included 110 samples from Khairahani Municipality, Chitwan, who were selected purposively through a convenience sampling procedure. Face-to-face interviews and a self-administrative questionnaire were used to collect information from the respondents who had been applying for at least 10 units of IPO. The findings revealed that the company’s performance and the sector’s performance were the major factors that influenced investors' perception. The majority of investors selected the microfinance industry because it provided a satisfactory return to them. A majority of the investors would like to hold stocks allotted in the IPO for a longer period of more than one year. Investors had a positive perception towards allocating 10 units of the IPO. However, they remained neutral in the case of their interest in the Book Building System. The Securities Board of Nepal (SEBON)’s awareness program before introducing the Book Building Pricing Method can be effective to develop people’s interest in Book Building System.